WHO ARE THE HUMANITIES FOR? DECOLONIZING THE HUMANITIES: With Peter Harrison, "Defining and Defending the Humanities"; Michael Ruse, "Willem Drees on the Humanities"; Douglas F. Ottati, "Theology among the Human Humanities"; Lisa L. Stenmark, "Who Are the Humanities For? Decolonizing the Humanities"; Donald L. Drakeman, "Some Second Thoughts about the Humanities"; and Willem B. Drees, "The Coherence and Character of the Humanities: A Reply to Critics.". Issue 3 (12th August 2021) - Stenmark, Lisa L.
Abstract: Drees makes a strong case for the importance of the humanities in the university, providing an excellent resource for anyone in the Western Academy. Its usefulness for those who want to work outside the West is limited, however, because he does not engage with literature that challenges its methods and disciplines. If we are to have a positive global impact, we need to do more than clarify existing boundaries, we need to blur them, beginning with an examination of inherent biases reflected in its history, structure, and content. This article focuses on one critique, a decolonial critique of the Western view that ontology precedes epistemology (an external reality produces knowledge). Outside the modern Western Academy, epistemologies create ontologies (epistemic creations/stories about the world give us a sense of the world and its materiality). I describe a relational understanding of knowledge and how this changes our understanding of the humanities and our epistemic responsibilities.